A new map of America from the latest authorities. - Cary, John, ca. 1754-1835 (J. Cary, 1806)
Map shows North America, South America, Greenland, Western Europe, and Africa. Areas of Native American habitation are noted and the Rocky Mountains are labeled "the Stony Mountains." Relief shown pictorially. Scale [ca. 1:42,000,000].